2020
DOI: 10.1515/ijamh-2020-0061
|View full text |Cite
|
Sign up to set email alerts
|

Contraception use: is everything played at first intercourse?

Abstract: ObjectivesThe rate of condom and other contraception use varies depending on social, personal and sexual characteristics. We present a study covering various contraceptive means, considering sexual orientation and considering a large panel of co-variables among Swiss resident young adults.MethodsData were obtained from a self-administrated national survey on sexual behavior. Participants (N=4703, 49% males) were divided into three groups based on the mean of contraception used at last intercourse: CONDOM (55.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…As research reported less contraception use during AI, we assessed contraception use. Contraception at first intercourse seems to have a considerable impact on the further use of contraception (Meuwly, Barrense-Dias, Auderset, & Suris Granell, 2020) and the rate of condom use at last intercourse allows quantifying current condom use (Noar, Cole, & Carlyle, 2006). Thus, we asked participants to report if they had used a condom at first and last intercourse.…”
Section: Independent Variablesmentioning
confidence: 99%
“…As research reported less contraception use during AI, we assessed contraception use. Contraception at first intercourse seems to have a considerable impact on the further use of contraception (Meuwly, Barrense-Dias, Auderset, & Suris Granell, 2020) and the rate of condom use at last intercourse allows quantifying current condom use (Noar, Cole, & Carlyle, 2006). Thus, we asked participants to report if they had used a condom at first and last intercourse.…”
Section: Independent Variablesmentioning
confidence: 99%